Mapping the elements of governance in international health security. - Gopalakrishnan, Shweta (Kansas State University, 2011)
Globalization has resulted in closer integration of economies and societies. It has contributed to the emergence of a new world order which involves a vast nexus of global and regional institutions, surrounded by transnational corporations, and non-governmental agencies seeking to influence the agenda and direction of international public policy. Health is a center point of geopolitics, security, trade, and foreign policy. Expansion in the territory of health and an increase in the number of health actors have profound implications for global health governance. Accordingly, the focus of the thesis is on endorsing the three core elements of governance proposed by Ackleson and Lapid, which comprises a system of (formal and informal) political coordination—across multiple levels from the local to the global—among public agencies and private corporations seeking to accomplish common goals and resolve problems through collective action. This shift in global governance has been prominent in the health sector with the formation of numerous public-private partnerships, coalitions, networks, and informal collaborations. In an effort to cope with the proliferation of players in the health sector, the World Health Organization has undergone gradual transformation in its governance framework. It is important to examine the evolution of the governance architecture of the WHO, as well as its effective application in the current global environment maintaining the organization’s legitimacy. This study tries to offer a comprehensive account of the WHO’s history, its successes and failures, as well as challenges and opportunities confronting the organization. Embracing public-private partnerships and formal-informal interactions does not simply fill governance gaps opened by globalization, but helps cluster in narrower areas of cooperation, where the strategic interests of multilateral organizations (e.g., the WHO), states, and transnational actors intersect. Global health problems require global solutions, and neither public nor private organizations can solve these issues on their own. The forms of governance based on the Acklesonian-Lapidian definition assist in accomplishing public health goals through shared decision-making and risk taking.
Keywords: Governance; Public-private partnerships; Health security; Globalization; Public Health (0573)